Secure internet of things (IoT) communication by blockchain technology - Ye, William Weisheng (Nanyang Technological University, 2020)
Rapid industrialisation has brought about various benefits to mankind and their economy. In recent years, the development of the Internet of Things surged exponentially and has brought about unimaginable changes and benefits for humans. Nonetheless, given that this rise of the Internet of Things is relatively new, there seems to be fewer rules and regulation encircling them. As such, there needs to be proper protection innovation such that the usage of these devices is guaranteed to be safe for daily practice, especially in the healthcare sector. This project will study the security limitations revolving the Internet of Things and delve into Blockchain technology as an alternative method to authenticate between the communication of the Internet of Things in the healthcare sector.